Edukasi Pencegahan dan Pemberantasan Penyalahgunaan dan Peredaran Gelap Narkotika di Jurusan Kebidanan Poltekkes Kemenkes Banjarmasin - Yuniarti; Hapisah; Kristiana, Efi; Januarsih; Suryanti (Rena Cipta Mandiri, 2025)
Drug abuse among adolescents is one of the most serious social problems in Indonesia. Drug use not only damages physical and mental health, but can also cause long-term social and economic damage. Based on data from the National Narcotics Agency (BNN), the number of teenagers involved in drug abuse continues to increase. Therefore, the prevention of drug use in adolescents is one of the top priorities in the effort to develop quality human resources. In order to overcome this problem, community service activities with the theme “Education on Prevention and Eradication of Narcotics Abuse and Illicit Trafficking in the Midwifery Department of the Poltekkes Kemenkes Banjarmasin” are carried out as an effort to provide education and awareness to adolescents and the surrounding community, so that they can avoid the dangers of drug abuse. Midwifery students showed positivity in their attitudes towards drug abuse. Some of the positive attitudes observed include: Midwifery students demonstrated positive attitudes toward drug abuse. Some of the observed positive attitudes include: students realized that drug abuse can damage their future, and they felt more responsible, at least for themselves.